LANGUAGE STYLE IN THE SONG LYRIC TAKING IT BACK BY MEGHAN TRAINOR - Mawaddah, Muftia Zakia; Nurmala, Dewi (PHILOLOGY Journal of English Language and Literature, 2024)
Language used to convey meaning in the form of communication, literature, and also in the creation of a written work. In the language there are language styles that are used to add aesthetics of speech or writing. This also applies to lyric of a song, because the lyrics are a written work. To find out the use of the language styles, the researcher analyzed the lyrics of the song Taking It Back by Meghan Trainor. This research use qualitative research and analysed the data with Gorys Keraf's theory which states that language style consists of two aspects that are language style based on the structure of sentences and language stylebased on meaning. There are nineteen songs that analysed thenseventeen types of language style that identificated in it. Repititionis widely identified in every lyrics.There are three types of Repition in this research that are Epizeuxis, Anaphora,and Epistroph. The researcher found sixteen another language style based on meaning with Denotation and Connotation meaning in each lyrics. There are Irony, Sinism, Sarcasm, Paradox, Antithesis, Hyperboles, Apofasis, Simile, Aliteration, Methapore, Asonantion, Eponym, Satire, Epitet, Personification and Alution.